Loss of Intra‐Epithelial Endocervical Gamma Delta (GD) 1 T Cells in HIV‐Infected Women. (15th December 2015) - Strbo, Natasa; Alcaide, Maria L.; Romero, Laura; Bolivar, Hector; Jones, Deborah; Podack, Eckhard R.; Fischl, Margaret A.
Abstract : Problem: Human gamma delta (GD) T cells play a well‐documented role in epithelial barrier surveillance and protection. Two subsets of GD T cells, defined by the use of either the Vdelta2 (GD2) or Vdelta1 (GD1) TCR, predominate. We hypothesized that endocervical GD T cells play important role in lower genital tract anti‐HIV immune responses. Method of study: HIV‐infected ( n = 18) and HIV‐uninfected ( n = 19) pre‐menopausal women participating in the WIHS cohort were recruited. Frequency and phenotype of GD T cells were determined in endocervical cytobrush samples and peripheral blood by multicolor flow cytometry. Results: We found depletion of GD2 cells in the blood of HIV‐infected women as well as significant decrease in the frequency of endocervical GD1 cells compared to uninfected women. Conclusion: We report for the first time, the GD1 cells are a predominant endocervical T‐cell subset that is significantly decreased in HIV‐infected women.